Prognostic value of the R-hf score in predicting length of hospital stay and in-hospital complications in patients with acute myocardial infarction - Linh, Duong Thi Thuy; Binh, Ho Anh; Thuan, Le Thi Bich; Trang, Le Thi Thu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Objective: This study aimed to evaluate the association between admission R-hf score and clinical outcomes, including hospital length of stay and in-hospital complications, in patients with acute myocardial infarction (AMI). Methods: A cross-sectional correlational study was conducted in 142 patients hospitalized with AMI at Hue Central Hospital between November 2024 and July 2025. The R-hf score was calculated using the formula: (eGFR × LVEF × hemoglobin)/NT-proBNP. Patients were stratified into four risk categories according to R-hf thresholds. Clinical variables, length of stay, in-hospital complications, and mortality were analyzed across R-hf groups. Results: The R-hf score was inversely associated with hospital length of stay (B = –0.002, p = 0.03). Patients with lower R-hf scores (<50) had significantly higher rates of in-hospital complications and mortality compared to those with scores >50 (p < 0.001 and p = 0.009, respectively). Higher R-hf scores were consistently observed among patients with favorable in-hospital outcomes (p < 0.001). Conclusion: The R-hf score, integrating key physiological domains (renal function, cardiac function, anemia, and volume load), is a clinically applicable and prognostically informative tool for early risk stratification in AMI. Its simplicity and objectivity support its use in routine clinical decision-making.